Ultra-high dose rate effect on circulating immune cells: A potential mechanism for FLASH effect?. (August 2020) - Jin, Jian-Yue; Gu, Anxin; Wang, Weili; Oleinick, Nancy L.; Machtay, Mitchell; (Spring) Kong, Feng-Ming
Highlights: Computer simulation showed a strong sparing effect on circulating immune cells. Threshold FLASH dose rate consistent with reported FLASH dose rate in animal studies. FLASH effect only with large dose per fraction. Threshold FLASH dose rate for humans one order of magnitude less than that for mice. Maybe not that challenging to develop a photon-based clinical FLASH-RT system. Abstract: Purpose: "FLASH" radiotherapy (RT) is a potential paradigm-changing RT technology with marked tumor killing and normal tissue sparing. However, the mechanism of the FLASH effect is not well understood. We hypothesize that the ultra-high dose rate FLASH-RT significantly reduces the killing of circulating immune cells which may partially contribute to the reported FLASH effect. Methods: This computation study directly models the effect of radiation dose rate on the killing of circulating immune cells. The model considers an irradiated volume that takes up A % of cardiac output and contains B % of total blood. The irradiated blood volume and dose were calculated for various A %, B %, blood circulation time, and irradiation time (which depends on the dose rate). The linear-quadratic model was used to calculate the extent of killing of circulating immune cells at ultra-high vs. conventional dose rates. Results: A strong sparing effect on circulating blood cells by FLASH-RT was noticed; i.e., killing of circulating immune cells reduced from 90% to 100% at conventional dose rates to 5–10% at ultra-high dose rates. The threshold FLASH dose rate was determined to be 40 Gy/s for mice in an average situation ( A % = 50%), consistent with the reported FLASH dose rate in animal studies, and it was approximately one order of magnitude lower for humans than for mice. The magnitude of this sparing effect increased with the dose/fraction, reached a plateau at 30–50 Gy/fraction, and almost completely vanished at 2 Gy/fraction. Conclusion: We have calculated a strong sparing effect on circulating immune cells by FLASH-RT, which may contribute to the reported FLASH effects in animal studies.